A blue-eyed Leptobrachium (Anura: Megophryidae) from Arunachal Pradesh, India - Sondhi, Sanjay; Ohler, Annemarie (Zootaxa, 2011)
A new species of Megophryidae, Leptobrachium bompu is described from Eaglenest Wildlife Sanctuary, Arunachal Pradesh, India. It is a medium sized member of the genus Leptobrachium. In life, the frog is distinguished by the combination of a series of morphological characters from its congeners. Its entirely greyish-blue coloured eyes differentiate the species from all other species in the genus but Leptobrachium waysepuntiense. The morphological comparison is based on a table of 16 characters discriminant in Leptobrachium species.